2017
DOI: 10.5194/acp-17-13921-2017
|View full text |Cite
|
Sign up to set email alerts
|

The role of meteorological conditions and pollution control strategies in reducing air pollution in Beijing during APEC 2014 and Victory Parade 2015

Abstract: Abstract. To control severe air pollution in China, comprehensive pollution control strategies have been implemented throughout the country in recent years. To evaluate the effectiveness of these strategies, the influence of meteorological conditions on levels of air pollution needs to be determined. Using the intensive air pollution control strategies implemented during the Asia-Pacific Economic Cooperation Forum in 2014 (APEC 2014) and the 2015 China Victory Day Parade (Victory Parade 2015) as examples, we e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 38 publications
1
43
1
Order By: Relevance
“…We find that during Ep1 and Ep4 the BTH areas are controlled by high pressure systems leading to stagnant air conditions and pollution accumulation, while during Ep3 (the APEC week) stronger northwestern winds associated a cold surge incursion prevail over BTH. Previous studies have also shown important influences from both emission reduction and meteorology on PM 2.5 concentrations in Beijing during the APEC week (Sun et al 2016, Zhang et al 2016, Gao et al 2017, Liang et al 2017. The observed mean PM 2.5 concentration is 48.9 μg m −3 in Beijing during APEC, and is about 60.3 μg m −3 lower than that in previous weeks (109.2 μg m −3 during 15 October-4 November 2014).…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…We find that during Ep1 and Ep4 the BTH areas are controlled by high pressure systems leading to stagnant air conditions and pollution accumulation, while during Ep3 (the APEC week) stronger northwestern winds associated a cold surge incursion prevail over BTH. Previous studies have also shown important influences from both emission reduction and meteorology on PM 2.5 concentrations in Beijing during the APEC week (Sun et al 2016, Zhang et al 2016, Gao et al 2017, Liang et al 2017. The observed mean PM 2.5 concentration is 48.9 μg m −3 in Beijing during APEC, and is about 60.3 μg m −3 lower than that in previous weeks (109.2 μg m −3 during 15 October-4 November 2014).…”
Section: Resultsmentioning
confidence: 66%
“…More recently, such practices have been further adopted to inhibit the formation of regional haze in Beijing and to reduce its potential damage to the society. Previous analyses of these temporary practices have shown that meteorological conditions are important for determining PM 2.5 concentration reductions and thus the effectiveness of emission control measurements (Guo et al 2016, Zhang et al 2016, Sun et al 2016, Liang et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have documented that the main causes of air pollution in eastern China are substantial pollution emissions and unfavorable meteorological conditions, which have been, respectively, viewed as internally and externally caused factors for air pollution (Guo et al, ; Z. Q. Li et al, ; Liang et al, ; Luo et al, ; Tong et al, ; Wu et al, ; Zhu et al, ). The discharges of pollutants, including industrial emissions, biomass burning, traffic exhaust, domestic heating, and other emissions caused by human activities, have caused the deterioration of air quality in eastern China (Guo et al, ; Jiang et al, 2012; Lei et al, ; Liao et al, ; Liu et al, , ; Lu et al, ; X. Y. Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Local meteorological parameters, such as the relative humidity, visibility, wind speed, and precipitation, modulate the formation of polluted haze episodes (Wang and He, ; Ding and Liu, ; Zheng et al ., ; Wang and Chen, ; Liang et al, ; Miao et al, ). Figure b shows that the visibility in Beijing has been declining, with a decrease of 1.1 km/decade in terms of the daily‐averaged visibility.…”
Section: Resultsmentioning
confidence: 99%